Assessing the Accuracy of PCR and Slit-Skin Smear Methods for Diagnosing Suspected Leprosy: An Evidence-Based Case Report - Ita Marlita Sari; Salsabilah Fahra Azzahra; Fatimatuz Zahro; Lita Salsabila; Siti Magfirotul 'Aini; Ratu Annisa Mutiara (Universitas Al Azhar Indonesia, 2026)
Leprosy (Hansen’s disease) is a chronic infectious condition caused by Mycobacterium leprae, affecting the skin, peripheral nerves, and mucosa. The slit-skin smear (SSS) is a standard diagnostic method but has limited sensitivity, especially in paucibacillary cases. Polymerase Chain Reaction (PCR) offers higher sensitivity by detecting M. leprae DNA, even in early or subclinical infections. This study aimed to compare the diagnostic accuracy of PCR and SSS in suspected leprosy cases. This Evidence-Based Case Report (EBCR) was developed through a structured literature search and critical appraisal of diagnostic accuracy studies using PubMed and Cochrane databases. Eligible cross-sectional studies comparing PCR and SSS were critically appraised for validity, relevance and applicability based on OCEBM and QUADAS-2. Two studies met the inclusion criteria and were analyzed based on sensitivity and specificity for M. leprae detection. Both studies demonstrated that PCR had markedly higher sensitivity than SSS. Khatoon et al. (2021) reported PCR detecting 66% of cases versus 34% by SSS, while Siwakoti et al. (2016) found 72% versus 18%, respectively. PCR exhibits advantages diagnostic accuracy compared to SSS, particularly for early or paucibacillary leprosy. Although more costly, PCR is recommended as a confirmatory tool to enhance early diagnosis and prevent disability.Keywords – Diagnosis, Leprosy, Mycobacterium Leprae, Polymerase Chain Reaction, Slit-Skin Smear